Assessing the effectiveness of decision aids for decision making in prostate cancer testing: a systematic review. Issue 10 (15th April 2015) - Ilic, Dragan; Jammal, Walid; Chiarelli, Pauline; Gardiner, Robert A.; Hughes, Suzanne; Stefanovic, Dana; Chambers, Suzanne K.; Dunn, Jeff
Abstract Background Prostate cancer is a leading disease affecting men worldwide. Conflicting evidence within the literature provides little guidance to men contemplating whether or not to be screened for prostate cancer. This systematic review aimed to determine whether decision aids about early detection of prostate cancer improve patient knowledge and decision making about whether to undergo prostate‐specific antigen testing. Methods Medline, EMBASE, CINAHL, PsychINFO, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects and Health Technology Assessment databases up until March 2014 were searched. All included randomised controlled trials were assessed for methodological quality. Clinical selection and assessment heterogeneity among studies prevented the pooling of data for meta‐analyses. Descriptive analyses of all included studies and comparison were performed. Results A total of 13 randomised controlled trials met the inclusion criteria. Significant heterogeneity was present for the design and implementation of decision aids including comparative interventions and outcomes. Eight studies were of a low methodological quality, with the remaining five of medium quality. Improvements in patient knowledge following use of a decision aid were demonstrated by 11 of the 13 included studies. Seven of 10 studies demonstrated a reduction in decisional conflict/distress. Three of four studies demonstrated no difference between a decision aid and information only in reducing decisional uncertainty. Three of five studies demonstrated an increase in decisional satisfaction with use of a decision aid. Conclusions Decision aids increase patient knowledge and confidence in decision making about prostate cancer testing. Further research into effective methods of implementation is needed. Copyright © 2015 John Wiley & Sons, Ltd.